2017
DOI: 10.1016/j.psychres.2016.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and mental health outcomes of potentially traumatic event exposure

Abstract: The aims were two-fold: to examine prevalence and correlates of lifetime potentially traumatic event (PTE) exposure and to explore the relationships between PTE exposure and mental health outcomes (i.e., trauma related distress, alcohol use quantity and frequency, depression symptoms, and anxiety symptoms) within a large sample of college freshmen. 6120 participants, consisting of three cohorts of incoming freshman at a large southeastern university, completed an online assessment battery measuring a multitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 71 publications
(77 reference statements)
5
44
0
Order By: Relevance
“…3,4 Current prevalence rates of PTE exposure and PTSD align with past studies of college students. 3,4,31,36 The findings also align with trends previously noted for PTE exposure and PTSD among females 32 , where the prevalence of PTSD in females is greater than that of males. 8,12,15,37 However, a recent study found that the effect of sex diminishes when other risk factors (e.g., pre-existing disorders, family history, personality features, coping strategies) are taken into consideration.…”
Section: Commentssupporting
confidence: 86%
See 2 more Smart Citations
“…3,4 Current prevalence rates of PTE exposure and PTSD align with past studies of college students. 3,4,31,36 The findings also align with trends previously noted for PTE exposure and PTSD among females 32 , where the prevalence of PTSD in females is greater than that of males. 8,12,15,37 However, a recent study found that the effect of sex diminishes when other risk factors (e.g., pre-existing disorders, family history, personality features, coping strategies) are taken into consideration.…”
Section: Commentssupporting
confidence: 86%
“…12 The current finding that being female is a significant correlate of probable PTSD after controlling for several other risk factors in young adults adds to our understanding of sex differences in risk and the growing literature on risk of PTSD in this age group. 36 Findings that depressive symptoms, interpersonal trauma, and total SLEs were associated with probable PTSD at the start of college align with previous reports from both adolescent and adult samples. Specifically, research on disorders comorbid with PTSD has shown that among youth with major depression, rates of comorbid PTSD range from 24-32%.…”
Section: Commentssupporting
confidence: 85%
See 1 more Smart Citation
“…Exposure to stressful and traumatic life events has been associated with negative psychological outcomes, such as posttraumatic stress disorder (PTSD) and major depressive disorder (MDD; Overstreet, Berenz, Kendler, Dick, & Amstadter, 2017; Pietrzak, Goldstein, Southwick, & Grant, 2011), though many exposed to such events demonstrate resilience. The field has, in more recent years, shown an appreciation of the study of resilient phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of psychological disorders is greater among university students than among their community counterparts (Hussain, Guppy, Robertson, & Temple, 2013). In a large sample of college freshmen, 81.8% reported experiencing at least one potentially traumatic event (PTE) and 8.7% reported experiencing four or more PTEs prior to entering college (Overstreet, Berenz, Kendler, Dick, & Amstadter, 2017). Moreover, a history of interpersonal PTE (e.g., physical assault, sexual assault, unwanted sexual situation) was associated with trauma related distress, anxiety and depressive symptoms, and increased alcohol use (Overstreet et al, 2017).…”
mentioning
confidence: 99%